Taenia laticollis and a potentially novel Taenia species from the Eurasian lynx (Lynx) in Northwestern China. (December 2021) - Liu, Gang; Zhao, Shanshan; Hornok, Sándor; Chen, Xueling; Wang, Suwen; Tan, Wenbo; Gu, Xinli; Wang, Yuanzhi
Abstract: The Eurasian lynx ( Lynx ) is a medium-sized wild cat species distributed throughout Eurasia. There has been no report on Taenia species (Cestoda: Cyclophyllidea) infecting this felid in China. In this study, 24 tapeworms were found in two Eurasian lynxes (#1 and #2) in Xinjiang Uygur Autonomous Region (XUAR), northwestern China. Based on the number, measurements and the shape of rostellar hooks, these tapeworms belong to two Taenia species. According to the number (n = 32) and length (185–194 μm) of small hooks, the first Taenia species (n = 1, found in #2 lynx) was identified as Taenia laticollis . Phylogenetically, this species was clustered with T . laticollis genotype C (JX860623) based on its cytochrome c oxidase subunit 1 ( cox1 ) and 16S r DNA sequences. The second Taenia species (n = 23, provisionally named as " Taenia sp.") may represent a potentially novel tapeworm species, because of its obvious differences in the shape and lengths (174–182 μm, 98–113 μm) of large and small rostellar hooks in comparison with ten taxonomically related species. Molecular and phylogenetic analyses of the cox1 gene revealed that " Taenia sp." has the highest rate of sequence identity (92.93%, 368/396 bp) with Taenia hydatigena reported from sheep ( Ovis aries ) in Slovakia. To sum up, a potentially novel tapeworm species, " Taenia sp.", is found in Eurasian lynx. In addition, T . laticollis was found for the first time in China. Graphical abstract: Image 1 Highlights: Taenia. laticollis was found for the first time in China. " Taenia sp." is a potential novel tapeworm species found in Eurasian lynx. Pairwise comparisons of the shape of the large rostellar hooks in Taenia sp. and the related species.